Sunday

January 25, 2015

January 25, 2015

Posted by **Robin** on Wednesday, August 8, 2007 at 1:36am.

5x - 2y = -5

y - 5x = 3

Substitute 5x + 3 for y in the first equation, and solve it for x.

Once you have x, use either of the two equations you wrote to solve for y.

**Answer this Question**

**Related Questions**

Algebra 1 - What is an equation of a line perpendicular to the line with ...

How do I do this.?(Math.) - Use the Substitution method to solve the system of ...

ALGEBRA 1!PLZ HELP! - Use the Substitution method to solve the system of ...

algebra2 - solve the systems of equation: First : 4x-2y = 2 Second: y = -4x-7 ...

algebra - 5x-2y=-5 y-5x=3 substitution Substitute 5x +3 for y in the first ...

math - Not sure about this... Need to solve by substitution 8x - 4y = 16 y = 2x...

substitution method - -3x+y=-5 x+2y=0 Your equations: -3x + y = -5 x + 2y = 0 ...

substitution method - -x-4y=-14 2x=y+1 Let's look at your two equations. -x - 4y...

Math - Solve the system by addition or substitution. 3x – 4y = 8 6x – 2y = 10 ...

Alg-Substitution (check plz) - k well i had to use substitution to find the ...